PENGARUH BANTUAN PROGRAM KELUARGA HARAPAN (PKH) DAN BLT DESA TERHADAP TINGKAT KESEJAHTERAAN MASAYARAKAT (STUDI PADA KELOMPOK PENERIMA MANFAAT (KPM) DI DESA TIRTA MAKMUR KECAMATAN AIR KUMBANG - Muharir Muharir; Reni Hariani (Integritas Jurnal Manajemen Profesional (IJMPRO), 2021)
The operational wheels of the Community Economy, to achieve the goals of Prosperity and prosperity must always be well managed, so that the process of achieving goals can run smoothly. This research uses quantitative research or all data is expressed in numbers. To obtain data to compile research, the authors conducted research on PKH Beneficiary Groups, Air Kumbang District, Kab. Banyuasin. To see the effect of PKH Social Assistance (X) on the Level of Welfare of the Village Community in Sideomulyo (Y), a simple linear regression analysis was used with the help of the SPSS program and a correlation test to test the relationship of the independent variable (X) to the dependent variable (Y) significantly. Based on regression analysis simple, the following equation can be generated: Y = a + bx = 33, 043 + 0.235 X It can be seen that the t value is 4.168, while the t table is 1.66412. In accordance with the t test formula, if t count> t table then Ho is rejected so that it can be seen that the PKH Assistance variable (X) 1 and Village BLT have a significant effect on the Level of Community Welfare (Y). while the results of the correlation test are as follows: correlation (r) = 0, 299 and probability (p) is significant at p <0, 05. According to the formula, if probability (p)> 0.05 then H0 is accepted, meaning that there is no relationship If the probability (p) <0.05 then H0 is rejected, it means that there is a relationship. For KPM PKH and BLT recipients in Tirta Mamkur Village, Air Kumbang District, Kabupate. Banyuasin, in order to use PKH and Village BLT assistance from the government as appropriate in accordance with applicable regulations. And because PKH is a conditional assistance from the government, KPM PKH must be able to properly optimize PKH assistance for its basic needs.